The systematic identification of organic compounds - Shriner, Ralph L.; Hermann, Christine K. F.; Morrill, Terence C.; Curtin, David Y.; Fuson, Reynold C. ([S.l.] : Wiley, 2004)
Dedicated to qualitative organic chemistry, this book explains how to identify organic compounds through step-by-step instructions. Topics include elemental analysis, solubility, infrared, nuclear magnetic resonance and mass spectra; classification tests; and preparation of a derivative. Most directions for experiments are described in micro or mini scales. Discusses chromatography, distillations and the separation of mixtures. Questions and problems emphasize the skills required in identifying unknown samples.